2016
DOI: 10.1590/1519-6984.07415
|View full text |Cite
|
Sign up to set email alerts
|

Quercetin and rutin as potential agents antifungal against Cryptococcus spp

Abstract: Amphotericin B is a fungicidal substance that is treatment of choice for most systemic fungal infections affecting as cryptococcosis the immunocompromised patients. However, severe side effects have limited the utility of this drug. The aim of this study was to evaluate the antifungal effect of the combination of amphotericin B with quercetin or rutin and as a protective of citotoxic effect. The antifungal activity to amphotericin B, quercetin and rutin alone and in combination was determined in Candida sp and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(46 citation statements)
references
References 29 publications
0
36
1
1
Order By: Relevance
“…Also, Qu et al [84] revealed the synergetic effect of quercetin-tetracycline combination treatment against multi-drug resistant (MDR) E. coli by disrupting the bacterial cell envelope, thus improving its permeability and cell lysis. Quercetin has been documented to improve the antifungal efficacy of amphotericin B against Candida sp and Cryptococcus neoformans strains by reducing its toxic effect [85]. Another study demonstrated the potent synergistic efficacy of quercetin against fluconazole-resistant strains of Candida tropicalis by enhancing mitochondrial membrane alterations that affect the mitochondrial respiratory function and inhibiting rhodamine-123 accumulation in the mitochondria [86].…”
Section: Combination Therapy Of Quercetin With Other Drugsmentioning
confidence: 99%
“…Also, Qu et al [84] revealed the synergetic effect of quercetin-tetracycline combination treatment against multi-drug resistant (MDR) E. coli by disrupting the bacterial cell envelope, thus improving its permeability and cell lysis. Quercetin has been documented to improve the antifungal efficacy of amphotericin B against Candida sp and Cryptococcus neoformans strains by reducing its toxic effect [85]. Another study demonstrated the potent synergistic efficacy of quercetin against fluconazole-resistant strains of Candida tropicalis by enhancing mitochondrial membrane alterations that affect the mitochondrial respiratory function and inhibiting rhodamine-123 accumulation in the mitochondria [86].…”
Section: Combination Therapy Of Quercetin With Other Drugsmentioning
confidence: 99%
“…However, the antifungal activities were lower against Penicillium funiculosum, P. ochrochloron, and Candida albicans. Several reports have indicated that rutoside, quercitrin, protocatechuic acid, and vanillic acid have antifungal activities [3,4,35,36].…”
Section: Discussionmentioning
confidence: 99%
“…The toxicity tests showed that quercetin protects red blood cells from amphotericin B-mediated hemolysis and toxicity. It was suggested that quercetin and rutin are potential agents to combine with amphotericin B in order to reduce the amphotericin dose to lessen side effects and improve antifungal efficacy (Oliveira et al, 2016). Rutin and aurapten isolated from Polygala paniculata plants common in Brazil has shown antifungal activity against (Johann et al, 2011).…”
Section: Antifungal Propertymentioning
confidence: 99%